Bile acid metabolism regulatory network orchestrates bone homeostasis - Tingwen Xiang; Zihan Deng; Chuan Yang; Jiulin Tan; Ce Dou; Fei Luo; Yueqi Chen (Elsevier, 2023)
Bile acids (BAs), synthesized in the liver and modified by the gut microbiota, have been widely appreciated not only as simple lipid emulsifiers, but also as complex metabolic regulators and momentous signaling molecules, which play prominent roles in the complex interaction among several metabolic systems. Recent studies have drawn us eyes on the diverse physiological functions of BAs, to enlarge the knowledge about the "gut-bone" axis due to the participation about the gut microbiota-derived BAs to modulate bone homeostasis at physiological and pathological stations. In this review, we have summarized the metabolic processes of BAs and highlighted the crucial roles of BAs targeting bile acid-activated receptors, promoting the proliferation and differentiation of osteoblasts (OBs), inhibiting the activity of osteoclasts (OCs), as well as reducing articular cartilage degradation, thus facilitating bone repair. In addition, we have also focused on the bidirectional effects of BA signaling networks in coordinating the dynamic balance of bone matrix and demonstrated the promising effects of BAs on the development or treatment for pathological bone diseases. In a word, further clinical applications targeting BA metabolism or modulating gut metabolome and related derivatives may be developed as effective therapeutic strategies for bone destruction diseases.